Dampak Teknologi Konservasi Terhadap Kualitas Tanah Di Kawasan Perbukitan Ponjong Gunung Kidul (Studi kasus evaluasi mikro DAS YUADP) = The Impact of Conservation Technology to The Soil Quality - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Abstract The aims of study was to evaluate the impact of introduced soil conservation technology on soil quality. The sudy was done onv three locations of farming system development in micro river basin scale. Each micro river basin covered an area of 10 ha, which was developed in 1993/1994 until 1996/1997. The sites were located in 3 hamlets, those were Ponjong (in Ponjong village), Munggur (in Sidorejo village) and Bedoyo Kulon (in Bedoyo village), Ponjong district, Gunung Kidul regency, Special Province of Yogyakarta. The study was conducted in 2000 after an evaluation on 1996. The study was done in two target areas. The first target was developed sites which appropriate to package technology, and the second one was comparable sites as a target impact (zero one relationship), at the time before, during and after the implementation of introduced technology. The field study consisted of soil morphology and its environmental condition, while laboratory observation determined physical and chemical properties of the soil that related to soil erosion proces. The results showed that introduced and adopted soil conservation technology of the farmer could improve the soil quality of famer's land. Improvements of soil quality on farmer's micro river basin were better than on farmer's non micro river basin.